Knowledge and Attitude about Labor Epidural Analgesia among Pregnant Women Attending Antenatal Clinic - Parajuli, Bashu Dev; Koirala, Megha; Joshi, Pankaj; Katuwal, Neeta; Shrestha, Amit; Singh, Shreejana; Rawal , Suniti; Shrestha, Anil (Journal of Nepal Health Research Council, 2024)
Background: Labour pain is one of the most painful experiences that a woman faces in her lifetime. There are various options for labour pain management. Epidural analgesia is the gold standard method for pain management during labour. In developing and under-developed countries there are many challenges to provide this service, a very important one being knowledge about epidural analgesia among the parturients and the physicians. Methods: A prospective cross-sectional study was carried out among 384 pregnant women attending Antenatal clinic of a tertiary level teaching hospital using pretested structured questionnaire prepared by a team of anaesthesiologists and obstetricians. Non-probability purposive sampling technique was used. The data was analysed by using SPSS version 20.0. Descriptive and inferential statistical methods were used for analysis. Results: Of the 384 pregnant women, only 29.4% had knowledge about some form of labour analgesia techniques and only 16% of the participants were aware of labour epidural analgesia. Also, only 6.2% were aware that epidural service is available at our hospital. Regarding acceptance, only 42.4% were willing to use epidural analgesia in their present pregnancy. Conclusions: The present study findings revealed that a significant number of participants had very limited knowledge about labour epidural analgesia and were also unaware of the availability of the service in our hospital. Educational programs need to be provided to all the pregnant women for enhancement of knowledge and awareness about epidural labour analgesia to increase its acceptability among them. Keywords: Acceptance; awareness; knowledge; labour analgesia.